Explanation of medical students' experiences of educational clinical supervision: A qualitative study - Soleiman Ahmady; Marzieh Sadat Minouei (Wolters Kluwer Medknow Publications, 2021)
CONTEXT: Clinical supervision is a mechanism that allows medical trainees to learn their profession through the practice of clinical activities alongside more experienced physicians who ensure safe and timely care delivery. Therefore, recognizing of medical students experiences as people who will provide health services to people in future can be an important source for gathering information and planning to improve the quality of clinical education. The aim of this study was to explain the experiences of medical students from clinical educational supervision. METHODS: This study was a qualitative content analysis conducted on 15 interns of the surgery and internal departments of medical and educational centers in Islamic Azad University Najafabad Branchin Isfahan, Iran to discover. The sampling method was purposive, and data were collected through semi-structured interviews in 2019. Data analysis was performed using a qualitative content analysis method with a conventional inductive approach. RESULTS: Five main categories and ninesubcategories were developed. The main categories include fundamental role, relaxed alertness, shadow education, toxic education, and abandoned educational. CONCLUSION: The educational clinical supervisory has an efficient performance in clinical teaching which needs to be more assessed and improved.